Solar Thermal Air Collector Based on a New Type of Selective Coating - Musiy, R.Y.; Midyana, G.G.; Makitra, R.G.; Vasyutin, J.M.; Khovanets, G.I.; Zaborowskiy, A.B. (Science and Innovation, 2024)
A solar thermal air collector operating on solar power on the principle of simultaneous ventilation and heating of facility has been designed on the basis of the best selective coating by optical characteristics and performance specifications. It can be used for holiday hotels, museums, wooden churches, warehouses, garages, houses, greenhouses, etc.